Increasing the health and nutritional outcomes of Rwanda's 'One cow per poor family' from a gender perspective - Colverson, Kathleen E. (University of Florida, 2018)
Presented by Kathleen Colverson (University of Florida), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.